Análise comparativa do relacionamento entre empresas e fornecedores da construção civil com empresas de outros ramos de atuação - Dandolin, Cleia Silmara de Lara (2020)
Strategic supplier management determines criteria for selection, evaluation, and development of suppliers, in addition to the administration of contracts and supplies. In this way, the management of suppliers aims to organize all the processes involving the suppliers of your business and the definition of criteria to support decision making regarding the selection of the best suppliers, considering those that meet all pre-established requirements. In addition, having an efficient supplier management also provides some proximity to these companies, facilitating the relationship, fostering collaborative innovation and, consequently, improving product costs and increasing the company’s competitiveness.The objective of this work is to analyze the relationship of construction suppliers and compare with industrial and service companies. To fulfill this objective, an applied quantitative research with exploratory character was developed through the field research. Questionnaires were applied to employees of construction companies and companies from other sectors such as service companies and companies linked to large industrial sectors, with questions related to their organizational characteristics and specific axes that determine the relationship such as trust, long term relationship and sharing of services. Information between customer and supplier. The data collected were submitted to descriptive and exploratory analysis to observe the divergent and similar characteristics between the two groups. The results of construction companies show gaps in the axis Trust, Information Sharing and mainly in the Long-Term Relationship axis.